The Legal Nature of the Crime of Electronic Hacking That Harms State Security a : A Comparative Study - Yousif , Fatma; Al-Ani, Mohammed (Journal of Legal Sciences, 2026)
Cyber-penetration is one of the most serious digital crimes threatening the stability and integrity of States' systems. For the purpose of espionage, sabotage or disruption of critical infrastructure, the research will show what the internal and external security of States is.As for its legal nature, the cybercrime has two different natures, one of which is the material aspect, which is when the information is stored on an electronic supporter, and the latter is the moral aspect, which is when the information is in a state of transfer or is present in the memory of the information system. In order to clarify the concept of breach of diamonds by the security of States, and also for this crime to materialize, its main pillars must be found s intention to harm the security of the State.